To the plasma wakefield excitation by a nonresonant sequence of relativistic electron bunches at plasma frequency above bunch repetition frequency - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Svistun, E.N.; Vesnovskaya, M.S. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
By using 2d3v code LCODE the investigation of plasma wakefield excitation by a nonresonant sequence of relativistic electron bunches for the case of bunch repetition frequency lower plasma frequency is carried out. Contrary to the case of nonresonant sequence with bunch repetition frequency higher plasma frequency the picture of field and bunches evolution is more complicated with no linear field growth. Nevertheless the asymmetry between the energy loss of decelerated bunches in the front half of beats and the energy gain of accelerated bunches in the rear half of beats, caused by different bunch-field coupling gives on average the growth of wakefield amplitude.